51.2k views
1 vote
Find the simplified form of the expression. Give your answer in scientific notation. (3*10^-6) (6*10^-8)

A.18 x 10^-13
B.1.8 x 10^-16
C.1.8 x 10^-13
D.1.8 x 10^-15

PLEASE ANSWER THIS QUICKLY!!!!!!!

User Goredwards
by
5.9k points

2 Answers

3 votes

Scientific notation:



m\cdot10^(n) where
1\leq m < 10\ \wedge\ n\in\mathbb{Z}



(3\cdot10^(-6))(6\cdot10^(-8))=(3\cdot6)(10^(-6)\cdot10^(-8))=18\cdot10^(-6+(-8))\\\\=18\cdot10^(-14)=(18\cdot10^(-14)\cdot10)/(10)=(18)/(10)\cdot10^(-14+1)=1.8\cdot10^(-13)


Answer: C.1.8 x 10^-13


Used:

Commutative Laws
a+b=b+a


a^n\cdot a^m=a^(n+m)


User DariusLau
by
5.3k points
4 votes

(3 * 10^-6)(6 * 10^-8) =


= (3 * 6) * (10^-6 * 10^-8)


= 18 * 10^-14


= 1.8 * 10^1 * 10^-14


= 1.8 * 10^-13

User Savanna
by
4.8k points